Label-free metabolic biomarkers for assessing valve interstitial cell calcific progression - Tandon, Ishita (Sci Rep, 2020)
Calcific aortic valve disease (CAVD) is the most common form of valve disease where the only available treatment strategy is surgical valve replacement. Technologies for the early detection of CAVD would benefit the development of prevention, mitigation and alternate therapeutic strategies. Two-photon excited fluorescence (TPEF) microscopy is a label-free, non-destructive imaging technique that has been shown to correlate with multiple markers for cellular differentiation and phenotypic changes in cancer and wound healing. Here we show how specific TPEF markers, namely, the optical redox ratio and mitochondrial fractal dimension, correlate with structural, functional and phenotypic changes occurring in the aortic valve interstitial cells (VICs) during osteogenic differentiation. The optical redox ratio, and fractal dimension of mitochondria were assessed and correlated with gene expression and nuclear morphology of VICs. The optical redox ratio decreased for VICs during early osteogenic differentiation and correlated with biological markers for CAVD progression. Fractal dimension correlated with structural and osteogenic markers as well as measures of nuclear morphology. Our study suggests that TPEF imaging markers, specifically the optical redox ratio and mitochondrial fractal dimension, can be potentially used as a tool for assessing early CAVD progression in vitro.